Editor-in-Chief Editorial - Reyes Carmona DDS, MSD, PhD, Jessie (Odovtos - International Journal of Dental Sciences, 2015)
The Editor-in-chief discussed briefly regarding the role of Research-Educational Model and academic publications in Dental Education. Moreover, the journal challenges and current issue topics are commented.